The histone deacetylase inhibitor romidepsin spares normal tissues while acting as an effective radiosensitiser in bladder tumours in vivo - Paillas, S; Then, C; Kilgas, S; Ruan, J; Thompson, J; Elliott, A; Smart, S; Kiltie, A (Elsevier, 2020)
Purpose: Muscle-invasive bladder cancer has a 40% to 60% 5-year survival rate with radical treatment by surgical removal of the bladder or radiation therapy–based bladder preservation techniques, including concurrent chemoradiation. Elderly patients cannot tolerate current chemoradiation therapy regimens and often receive only radiation therapy, which is less effective. We urgently need effective chemotherapy agents for use with radiation therapy combinations that are nontoxic to normal tissues and tolerated by elderly patients.